Impact of galacto-oligosaccharides on prebiotic potential in the intestinal microbiota fermentation and health status in an animal model - BAJWA, Amna Ashraf (2023)
The present study was conducted to assess selected galacto-oligosaccharides (GOS) effects on short-chain acids (SCFA), microbiota variability in in vitro, and health benefits using an animal model. In the in-vitro anaerobic batch, fermentation was applied to different groups divided by a varied amount of GOS sources, mixtures, and prebiotics. Results reported that SCFA for inulin contributed significantly higher for acetic, propionic, and butyric acids, and resistant starch (RS) showed a non-significant effect for acetic and propionic acids whereas the combined effect of GOS and RS showed higher values for parameters. For bacterial enumeration of bifidobacteria compared to individual GOS, synergistic effects were documented. The Sprague-Dawley rats given GOS under western diet influence relative to a high-fat diet alone observed after 1 and 4 weeks documented significant levels for acetic and butyric acid production, whereas body and organ weights for cecum tend to increase after 4 weeks of dietary intervention (p<0.05). Microbiome data using gene sequencing revealed a higher proportion of firmicutes and lower Bacteroides in control rats, which means Lachnospiraceae family abundances were higher in HF+GOS group. Overall, GOS fermentation showed an increment in the bifidobacterial population and tend to raise levels of SCFA in rats fed on a high-fat diet alone, whereas non-significant variation was reported in microbiome diversity after intervention. The present study was conducted to assess selected galacto-oligosaccharides (GOS) effects on short-chain acids (SCFA), microbiota variability in in vitro, and health benefits using an animal model. In the in-vitro anaerobic batch, fermentation was applied to different groups divided by a varied amount of GOS sources, mixtures, and prebiotics. Results reported that SCFA for inulin contributed significantly higher for acetic, propionic, and butyric acids, and resistant starch (RS) showed a non-significant effect for acetic and propionic acids whereas the combined effect of GOS and RS showed higher values for parameters. For bacterial enumeration of bifidobacteria compared to individual GOS, synergistic effects were documented. The Sprague-Dawley rats given GOS under western diet influence relative to a high-fat diet alone observed after 1 and 4 weeks documented significant levels for acetic and butyric acid production, whereas body and organ weights for cecum tend to increase after 4 weeks of dietary intervention (p<0.05). Microbiome data using gene sequencing revealed a higher proportion of firmicutes and lower Bacteroides in control rats, which means Lachnospiraceae family abundances were higher in HF+GOS group. Overall, GOS fermentation showed an increment in the bifidobacterial population and tend to raise levels of SCFA in rats fed on a high-fat diet alone, whereas non-significant variation was reported in microbiome diversity after intervention.